2007
DOI: 10.1097/01.hnp.0000280931.75883.ae
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Healing Touch, Coaching, and a Combined Intervention on Comfort and Stress in Younger College Students

Abstract: Three nursing interventions to increase total comfort and reduce stress-related events in young college students experiencing stress were compared. Healing Touch, coaching, and a combination of both, were compared to a waitlist. On comfort and stress, Healing Touch had better immediate results, while coaching had better carryover effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…1,2 Coaching also has been a tool for faculty development 3 and professional development. 2 Several health fields have reported the application of coaching in developing nurse leaders, 1,2,4-6 nursing staff, 4,7 medical residents, 8 dentists, 9 physicians, 3,10,11 students, 12 pharmacists, 13 and pharmacy leaders. 14 Coaching also has been used in reducing work-related stress and improving work-life balance.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Coaching also has been a tool for faculty development 3 and professional development. 2 Several health fields have reported the application of coaching in developing nurse leaders, 1,2,4-6 nursing staff, 4,7 medical residents, 8 dentists, 9 physicians, 3,10,11 students, 12 pharmacists, 13 and pharmacy leaders. 14 Coaching also has been used in reducing work-related stress and improving work-life balance.…”
Section: Introductionmentioning
confidence: 99%
“…Theory-based empirical research (use this model to design comfort studies). Reprinted with permission from Kolcaba (2007). 16 research, and dissemination.…”
Section: Comfort Theorymentioning
confidence: 97%
“…Comfort theory evolved from Kolcaba's early concept analysis and TS of comfort as a desirable outcome of nursing care as determined by the patient. 4 She demonstrated that patient comfort could be measured through patient questionnaires [5][6][7][8] and later verbal rating scales (VRS), 9,10 and that these measurements were sensitive enough to show a significant increase in comfort over time, given an effective intervention. [5][6][7][8][9]11 Moreover, patient comfort was found to be predictive of which patients achieved their selected goals related to health.…”
Section: Review Of Literaturementioning
confidence: 99%
“…That particular study examined a group of young college students and found that after receiving HT there was an immediate decrease in overall stress at the end of the study (Dowd, Kolcaba, Steiner, & Fashinpaur, 2007).…”
Section: Healing Touch: Pain Anxiety and Stressmentioning
confidence: 97%